Bias in Forensic Examination - A. V. Kokin (Теория и практика судебной экспертизы, 2022)
The article discusses various aspects of the influence of bias on the formation of conclusions of a forensic expert. The author highlights that the negative effect of bias is especially significant in identification examinations, where the conclusions are based on subjective interpretations of the results of marks comparison (toolmark, fingerprint, firearms examinations, and others). The author also notes that there is no clear border between objectivity and subjectivity in forensic examinations. All types of forensic examinations exist in an objective-subjective continuum, which causes different conclusions’ reliability. Since subjectivity is the basis for bias formation, minimizing its impact can be achieved in several ways – increasing the “transparency” of documenting the research process, technical analysis and verification of an expert’s opinion, applying quantitative criteria for evaluating the matching features in the compared marks. The most logical way to reduce the influence of bias is to eliminate the causes that give rise to this phenomenon. These are the excessive contextual information provided to the expert, the expert’s deviation from the requirements of methodological recommendations in examining the objects, and various external and internal influences.